Pleiotropic effect of a point mutation in the yeast SUP4-o tRNA gene: in vivo pre-tRNA processing in S. cerevisiae. - Wilhelm, M L (1992)
The expression of mutant tyrosine-inserting ochre suppressor SUP4-o tRNA genes in vivo in S. cerevisiae was examined as a basis for further studies of tRNA transcription and processing. In vivo yeast precursor tRNAs have been identified by filter hybridization and primer extension analysis. We have previously shown that a mutant SUP4-o tRNA gene with a C52----A52 transversion at positive 52 (C52----A52(+IVS) allele) was transcribed but that the primary transcript was not processed correctly. We show here that 5' and 3' end processing as well as splicing are defective for this mutant but that the 5' end processing is restored when the intron is removed from the gene by oligonucleotide directed mutagenesis (C52----A52(-IVS) allele). Our results imply that the C52----A52 transversion by itself cannot account for the lack of susceptibility to RNase P cleavage but that the overall tertiary structure of the mutant tRNA precursor is destabilized by the intron/anticodon stem. A second consequence of the C52----A52 transversion is to prevent complete maturation of the tRNA precursor at its 3' end since intermediates containing incompletely processed 3' trailers accumulate in the yeast cells transformed with the C52----A52(-IVS) allele. A correct structure of the T stem might therefore define a structural feature required for the recognition of the 3' processing activity.